Comparison of freehand‐navigated and aiming device‐navigated targeting of liver lesions. Issue 1 (8th July 2013) - Wallach, D.; Toporek, G.; Weber, S.; Bale, R.; Widmann, G.
Abstract Background Accurate needle placement is crucial for the success of percutaneous radiological needle interventions. We compared three guiding methods using an optical‐based navigation system: freehand, using a stereotactic aiming device and active depth control, and using a stereotactic aiming device and passive depth control. Methods For each method, 25 punctures were performed on a non‐rigid phantom. Five 1 mm metal screws were used as targets. Time requirements were recorded, and target positioning errors (TPE) were measured on control scans as the distance between needle tip and target. Results Time requirements were reduced using the aiming device and passive depth control. The Euclidian TPE was similar for each method (4.6 ± 1.2–4.9 ± 1.7 mm). However, the lateral component was significantly lower when an aiming device was used (2.3 ± 1.3–2.8 ± 1.6 mm with an aiming device vs 4.2 ± 2.0 mm without). Discussion Using an aiming device may increase the lateral accuracy of navigated needle insertion. Copyright © 2013 John Wiley & Sons, Ltd.